2016
DOI: 10.1056/nejmoa1604344
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Long-Term Oxygen for COPD with Moderate Desaturation

Abstract: BACKGROUND Long-term treatment with supplemental oxygen has unknown efficacy in patients with stable chronic obstructive pulmonary disease (COPD) and resting or exercise-induced moderate desaturation. METHODS We originally designed the trial to test whether long-term treatment with supplemental oxygen would result in a longer time to death than no use of supplemental oxygen among patients who had stable COPD with moderate resting desaturation (oxyhemoglobin saturation as measured by pulse oximetry [SpO2], 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(120 citation statements)
references
References 29 publications
1
114
0
5
Order By: Relevance
“…In patients with moderate resting (89%-93%) or exercise-induced arterial desaturation (80%-90%), long-term oxygen does not improve outcomes (A, GOLD). 6 Recommendation 14. Consider longterm oxygan after a risk assessment of fall and burn risk.…”
Section: Nonpharmacologic Copd Managementmentioning
confidence: 99%
“…In patients with moderate resting (89%-93%) or exercise-induced arterial desaturation (80%-90%), long-term oxygen does not improve outcomes (A, GOLD). 6 Recommendation 14. Consider longterm oxygan after a risk assessment of fall and burn risk.…”
Section: Nonpharmacologic Copd Managementmentioning
confidence: 99%
“…But a randomized controlled trial demonstrated that most patients with COPD (ie, all except a subset of the highest risk patients) derive no benefit from the oxygen-not in terms of survival, hospital admissions, or quality of life. 2 At the same time, oxygen significantly increases the risk of burns for patients; 3 it is costly to the patient; 4 and it is a burden that the patient literally has to carry that impairs their ability to socialize. 4 Other well-publicized examples of low-value care include hormone replacement therapy to prevent cardiovascular events among perimenopausal women; 5 antibiotics to treat viral upper-respiratory infections; and diagnostic imaging for simple lower-back pain.…”
Section: Equity Underuse and Overusementioning
confidence: 99%
“…Oxygen is one of several strategies used to reduce breathlessness 6 and has been shown to increase the survival for people with Chronic Obstructive Pulmonary Disease (COPD) with severe hypoxaemia. However, oxygen's benefits are less clear for people with different diseases and for those people who are not hypoxemic, or only mildly so, and in some situations, may be no better than medical air 7,8 . Nevertheless, clinicians commonly prescribe oxygen in the palliative setting and there is evidence that non-clinical factors can influence prescribing patterns.…”
Section: Introductionmentioning
confidence: 99%